Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Experimental trace element partition coefficients for upper mantle pyroxenites coexisting with H2O with CO2, NaCl and NH3 fluids - Matthew J. M. Phillips; Svyatoslav S. Shcheka; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2026)
Experimental determinations of trace element distribution between rocks/minerals and fluids at mantle pressures and temperatures have concentrated on eclogite and on fluids containing H 2 O with or without the addition of NaCl. Here we present data for websterite (pyroxenite) coexisting with five different fluids: H 2 O, H 2 O+CO 2 , H 2 O+NaCl, H 2 O+CO 2 +NaCl and H 2 O+NH 3 . All experiments were conducted at 1.5 GPa and 800˚C using glassy carbon fluid traps that were kept in a frozen state following experiments until trace elements in the fluid traps were analysed by laser cryoablation-ICP-MS. Results show that Rb, Ba, Sr, Pb and Li are fluid-mobile, with lower rock/fluid partition coefficients (D Rock/Fluid ) for all mixed fluids relative to pure H 2 O. Lowest values (0.0004–0.123) are found for H 2 O+NH 3 fluids. Almost all for the REE are 2 O+CO 2 +NaCl and H 2 O+NH 3 fluids, as are the HFSE, which also show lower D Rock/Fluid than for eclogites, with or without NaCl. Re and Pt are fluid-mobile, with D Re Pt and lowest values for both in H 2 O+CO 2 fluids. The first row transition elements show D-values ranging from 0.0004 to 2.88 with only 4 of 35 data points > 1. D Rock/Fluid increase in the order Cu Rock/Fluid ,particularly low-Al clinpyroxenes.

A common mantle source for strongly silica-undersaturated magmas: Insights from Zn-Fe isotopes in kimberlites - Ronghua Cai; Andrea Giuliani; Paolo A. Sossi; Tian-Hao Wu; Yongsheng He; D. Graham Pearson; Stephen F. Foley; Jingao Liu (Earth and Planetary Science Letters, 2026)

Mg isotopes and in-situ Rb Sr dating reveal carbonate-rich and carbonate-poor sediments in mantle sources of lamproites beneath the North China Craton - Kaizhang Yu; Yongsheng Liu; Wei Chen; Chunfei Chen; Chutian Shu; Stephen F. Foley; Jixing Li; Zhaochu Hu (Chemical Geology, 2025)

Kamafugites - Francesca Innocenzi; Sara Ronca; Samuele Agostini; Vincenza Guarino; Stephen F. Foley; Michele Lustrino (Earth-Science Reviews, 2025)

Asthenospheric flow and lithospheric erosion driving the outward growth of the northeastern Tibetan Plateau - Chutian Shu; Xiaoping Long; Stephen F. Foley; Kaizhang Yu; Zhuoying Zhang; Zheng-Xiang Li; Luc S. Doucet; Qiang Xu (Science Bulletin, 2025)

The mineralogical distribution of Ni in mantle rocks controls the fertility of magmatic Ni-sulfide systems - Daryl E. Blanks; David A. Holwell; Isra S. Ezad; Andrea Giuliani; Marco L. Fiorentini; Stephen F. Foley (Mineralium Deposita, 2025)
Mantle-derived mafic-ultramafic melts are the primary host for magmatic Ni-Cu-Co-PGE deposits. One common assumption about this mineral system is that Ni-fertility is a product of high-degree melting of anhydrous mantle peridotites, including a substantial contribution from olivine. However, in metasomatised mantle rocks, which partially melt at lower temperatures than anhydrous peridotites, Ni is hosted by a range of minerals, including hydrous phases such as phlogopite and amphibole in addition to olivine and orthopyroxene. The lower melting point of these hydrous phases makes Ni in phlogopite a potentially significant contributor to the Ni enrichment of mantle melts from metasomatised assemblages. We analyse a suite of phlogopite-bearing mantle rocks which display variably metasomatised assemblages using SEM mapping to quantify mineral assemblages, and laser ablation ICP-MS to determine the Ni deportment in these rocks. Phlogopite in hydrous peridotites contains 859–1126 ppm Ni equating to ~ 12% of the bulk Ni content in an assemblage containing 25% phlogopite. Mica-Amphibole-Rutile-Ilmenite-Diopside rocks contain phlogopite with 428–715 ppm Ni, which can contribute up to 50% of the bulk Ni in an assemblage of 30% phlogopite. At temperatures below the dry peridotite solidus (< 1300 °C), phlogopite can become a significant contributor of Ni to mantle melts. Thus, partial melting of metasomatised hydrous assemblages can produce Ni-fertile mafic-ultramafic magmas without substantial temperature perturbations such as those associated with mantle plumes. This opens up a range of geodynamic settings for Ni sulfide fertility, away from large igneous provinces and their plumbing systems, into settings such as orogenic belts, arcs and intraplate rifts.

Hydrous minerals are sinks for first row transition elements in the mantle: An experimental partitioning study - Isra S. Ezad; Joshua J. Shea; Stephen F. Foley (Chemical Geology, 2025)

Melting of amphibole-apatite-rich metasomes in the continental mantle and comparison of melt compositions with natural igneous rocks - Stephen F. Foley; Isra S. Ezad; Chutian Shu; Michael W. Förster (Lithos, 2025)

Recent advances made by reaction experiments on melting of heavily metasomatized hydrous mantle - Dejan Prelević; Michael W. Förster; Stephan Buhre; Fatma Gülmez; Tobias Grützner; Yu Wang; Stephen F. Foley (Earth-Science Reviews, 2024)

Fluid loss to the fore-arc controls the recycling efficiency of nitrogen in subduction zones - Michael W. Förster; Chunfei Chen; Stephen F. Foley; Olivier Alard; Gregory M. Yaxley (Chemical Geology, 2024)

Lithospheric hydrous pyroxenites control localisation and Ni endowment of magmatic sulfide deposits - Isra S. Ezad; Daryl E. Blanks; Stephen F. Foley; David A. Holwell; Jason Bennett; Marco L. Fiorentini (Mineralium Deposita, 2024)

Calcium isotope compositions of subduction-related leucite-bearing rocks: Implications for the calcium isotope heterogeneity of the mantle and carbonate recycling in convergent margins - Huange Ren; Martina Casalini; Sandro Conticelli; Chunfei Chen; Stephen F. Foley; Lanping Feng; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

Calcium isotopes track volatile components in the mantle sources of alkaline rocks and associated carbonatites - Chunfei Chen; Stephen F. Foley; Sebastian Tappe; Huange Ren; Lanping Feng; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

Origin of carbonate melts in orogenic belts by anatexis of downthrust carbonate sediments - Chengyuan Wang; Stephen F. Foley; Yongsheng Liu; Yu Wang; Yi-Gang Xu (Earth and Planetary Science Letters, 2023)

Tightly coupled Ca-Zn-Sr isotope co-variations in basalts caused by recycled calcium carbonate in the mantle source - Detao He; Yongsheng Liu; Frédéric Moynier; Stephen F. Foley; Chunfei Chen; Yangtao Zhu; Xinting Lü; Ganglan Zhang; Keqing Zong (Chemical Geology, 2023)

Volcanic phosphorus supply boosted Mesozoic terrestrial biotas in northern China - Chao Ma; Yanjie Tang; Ross N. Mitchell; Yongfei Li; Shouliang Sun; Jichang Zhu; Stephen F. Foley; Min Wang; Chenyang Ye; Jifeng Ying; Rixiang Zhu (Science Bulletin, 2023)

Transition from tholeiitic to alkali basalts via interaction between decarbonated eclogite-derived melts and peridotite - Qiuhong Xie; Zhaochong Zhang; Stephen F. Foley; Chunfei Chen; Zhiguo Cheng; Yu Wang; Weiliang Kong; Yiwen Lv; M. Santosh; Qizhen Jin; Lukáš Krmíček; Xiangkun Zhu (Chemical Geology, 2023)

Application of Ge/Si ratios to ultramafic alkaline rocks using a novel LA-ICP- MS/MS method - Matthew J.M. Phillips; Stephen F. Foley; Olivier Alard (Chemical Geology, 2023)

The effect of COH fluids on partial melting of eclogite and lherzolite under moderately oxidizing and reducing conditions - Zairong Liu; Arno Rohrbach; Carla Tiraboschi; Stephen F. Foley; Jasper Berndt; Stephan Klemme (Chemical Geology, 2023)

Insights into the petrogenesis of the West Kimberley lamproites from trace elements in olivine - A. Lynton Jaques; Stephen F. Foley (Mineralogy and Petrology, 2018)

Petrology of spinel lherzolite xenoliths from Youkou volcano, Adamawa Massif, Cameroon Volcanic Line: mineralogical and geochemical fingerprints of sub-rift mantle processes - Merlin Patrick Wagsong Njombie; Robert Temdjim; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2018)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Trace element variations in olivine phenocrysts from Ugandan potassic rocks as clues to the chemical characteristics of parental magmas - Stephen F. Foley; Dorrit E. Jacob; Hugh St. C. O’Neill (Contributions to Mineralogy and Petrology, 2011)

Continuous cratonic crust between the Congo and Tanzania blocks in western Uganda - Klemens Link; Daniel Koehn; Matthias G. Barth; John V. Tiberindwa; Erasmus Barifaijo; Kevin Aanyu; Stephen F. Foley (International Journal of Earth Sciences, 2010)

Trace element partitioning in the granulite facies - Franziska Nehring; Stephen F. Foley; Pentti Hölttä (Contributions to Mineralogy and Petrology, 2010)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Phase relations and fractionation sequences in potassic magma series modelled in the system CaMgSi 2 O 6 -KAlSiO 4 -Mg 2 SiO 4 -SiO 2 -F 2 O −1 at 1 bar to 18 kbar - Stefan Melzer; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2000)